2017
DOI: 10.1002/lno.10620
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistency for the niche breadth invasion success hypothesis in aquatic invertebrates

Abstract: Comparison of highly successful and less successful invasive species can highlight traits that are associated with invasion success, and indicate the associated risk of further establishment or invasion from novel species. We compared variation in d revealed, in most cases, greater niche breadth in the more successful species of tunicate but the less successful species of waterflea and oyster. Comparison with the literature suggested that a broad dietary niche is less crucial for widespread distribution of aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…A larger SEA indicates greater diet breadth, as reported by previous studies 5 , 45 . A larger CR is expected in food webs containing multiple basal resources with varying δ 13 C values, implying a broad total range of exploited resources 27 , 31 .…”
Section: Methodssupporting
confidence: 80%
“…A larger SEA indicates greater diet breadth, as reported by previous studies 5 , 45 . A larger CR is expected in food webs containing multiple basal resources with varying δ 13 C values, implying a broad total range of exploited resources 27 , 31 .…”
Section: Methodssupporting
confidence: 80%
“…Positive relationships between niche breadth and conspecific population density (Faulks et al, 2015) have been reported, as have interspecific interactions involving related native species (Tarjuelo et al, 2017). The negative relationship between niche breadth of a native species and abundance of an invasive species has not been documented systematically in previous studies, although niche characteristics are known to be a factor in species invasions (Comte et al, 2017;Jackson et al, 2016;Pettitt-Wade et al, 2015, 2018. Niche shifts and divergences have also been described in earlier studies of gammarid communities where TA B L E 1 Results of multiple regression analyses of abundance of Gammarus pulex and G. duebeni celticus on measurements of variation in environmental heterogeneity in the River Lagan system (see Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Jackson et al (2016) demonstrated constriction of dietary niche in an invasive crab competing with a functionally similar native species. Pettitt‐Wade et al (2018) also highlight the inconsistency in the link between niche breadth and invasion success focusing on differences between fish and aquatic invertebrates. Herkül et al (2016) suggest that an invasive gammarid G .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is some evidence that body size of detritovores, particularly millipedes, can be related to feeding traits (Semenyuk & Tiunov, 2019). In predators, more homogeneous diets and smaller niches have been documented for species of larger body size (Zhao et al, 2014;Bašić & Britton, 2015;Pettitt-Wade et al, 2018). In contrast, Sanders et al (2015) observed increases in niche size with increasing body size in several spider species, assuming that individuals can potentially consume a wider range of prey as the predator grows.…”
Section: Introductionmentioning
confidence: 99%